2018
DOI: 10.1177/0163443718818354
|View full text |Cite
|
Sign up to set email alerts
|

Is public service broadcasting a threat to commercial media?

Abstract: This article asks to what extent public service broadcasting’s online news service resembles that of commercial media. The context of this inquiry is claims of ‘out-crowding’ facing public service broadcasters across Europe. In Norway, commercial players in this debate accuse the public service broadcaster, NRK, of being too similar to competitors in the private sector for commercial operators to attain sustainable revenues in the online realm. To ascertain the extent to what these claims are warranted, this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Benson, 2018)) and localism characteristics (contributing to differentiate journalism (cf. Sjøvaag et al, 2018)). On the other hand, the presence of NRK's regional offices points to the public service broadcaster playing a positive role in hard news and political journalism at the local level.…”
Section: Discussionmentioning
confidence: 99%
“…Benson, 2018)) and localism characteristics (contributing to differentiate journalism (cf. Sjøvaag et al, 2018)). On the other hand, the presence of NRK's regional offices points to the public service broadcaster playing a positive role in hard news and political journalism at the local level.…”
Section: Discussionmentioning
confidence: 99%
“…Intervening policy streams helped frame the definition of the problem also in the NRK's case, for example, the ongoing discussion of how to aid a struggling national press, which resulted in a separate decision on zero-rated VAT on digital media in 2016 (Sundet, Ihlebaek, and Steen-Johnsen 2019;Enli et al 2019), and the ongoing discussion of how to handle the commercial public broadcaster TV 2's financial situation. These intervening policy streams contribute to a problem construction that initially circulates across the field, particularly that the NRK's broad remit is a problem threatening online business models (see also Sjøvaag, Pedersen, and Owren 2019). A report from the Media Businesses' Association claimed that the NRK was 'a giant in the Norwegian media market', and, if not curbed, would reduce media diversity (MBL 2014a, 4) and one tabloid claimed: 'NRK is about to become the only fat sow in the Norwegian media industry' and 'NRK is as much a threat to pluralism as it is a guarantor' (Ramnefjell 2015).…”
Section: Phase 1: Positioning For Radical Changementioning
confidence: 99%
“…Contrary to an ongoing narrative of doom for legacy media, several studies have shown that public service institutions remain a significant force in many countries (Horowitz and Clark 2014;Tambini 2015), continue to engage a broad range of stakeholders (Isofides 2010;Ibarra, Nowak, and Kuhn 2015), and remain dependent on regulatory decisions in regional or national contexts (Donders 2012;Brevini 2013). In the article, we are also informed by studies focusing specifically on media policy reviews and criticism of public service broadcasting in the UK and Norway (Blumler 2016;Gibbons 2017;D'Arma 2018;Sjøvaag, Pedersen, and Owren 2019;Enli et al 2019;Sundet, Ihlebaek, and Steen-Johnsen 2019). However, few studies apply a uniform comparative framework to two cases, and articles combining stakeholder perspectives with multiple streams are almost nonexistent (see, however, Herzog and Karppinen 2014;Steemers 2017).…”
mentioning
confidence: 99%
“…In these debates, NRK was no longer presented as a guarantor of democracy, but as a threat. However, when private and commercial players (once again) claimed that NRK was reducing their market position by producing ‘free’, high-quality content on all available platforms NRK framed itself specifically as a bulwark against the ‘global super players’, such as Netflix, YouTube, and Facebook that had by then become very salient (Dagens Næringsliv, 2013b; see also Dagens Næringsliv, 2015a, 2016d; Sjøvaag et al, 2018). Furthermore, NRK stressed that ‘global super players’ were a threat not only to NRK but also to all national media, thus widening the frame to include its competitors.…”
Section: Psb In the Digital Agementioning
confidence: 99%